Potential of sunflower, castor bean, common buckwheat and vetiver as lead phytoaccumulators - Jailson do C. Alves; Adailson P. de Souza; Mônica L. A. Pôrto; Renildes L. F. Fontes; Jandeilson Arruda; Luciano F. Marques (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Studies concerning the tolerance, absorption and distribution of heavy metals in plants are essential for the success of phytoremediation programs. The present study was carried out in order to evaluate the potential of the sunflower, castor bean, common buckwheat and vetiver as lead phytoaccumulators. The species were grown in nutrient solution containing increasing doses of Pb (0, 50, 100, 200 and 400 mg L-1) during a 30-day exposure period. A completely randomized split-plot design was used, with a 4 x 5 factorial and three replicates. Significant reductions of dry matter of the root, shoot and whole plant were found in the all species under study as a function of the increased Pb doses. Vetiver showed higher tolerance to Pb contamination; sunflower and castor bean had intermediate tolerance and the common buckwheat proved to be the most sensitive species. The concentration and total content of Pb in plant compartments were significantly affected by the increased Pb doses in solution, and higher accumulation of this element was observed, in general, in the roots of the studied species. Common buckwheat proved to be not much promising for Pb-phytoremediation programs; sunflower showed potential for Pb phytoextraction and castor bean and vetiver were the most appropriate for Pb phytostabilization.